Urgent considerations on renal immune-related adverse events in oncology practice - Lv, Wen-Qing; Lu, Jing-Yao; Li, Jun; Lv, Dao-Yuan; Ke, Qi (Frontiers in Immunology, 2026)
In recent years, immune checkpoint inhibitors (ICIs) have emerged as a critical component of hematological malignancies and solid malignant tumors therapy. However, clinical practice has revealed that these agents may induce immune-related adverse events (irAEs). Notably, renal irAEs stands out as a significant clinical concern, frequently necessitating treatment discontinuation and thereby enabling tumor progression. Renal irAEs constitutes a critical consideration for patients with cancer complicated by chronic kidney disease (CKD). This review systematically examines the immunologic pathogenesis of ICIs-induced renal disease, susceptibility genes, non-invasive biomarkers, and efficient intervention strategies. It further analyzes the critical considerations regarding renal irAEs that oncologists must address, based on real-world evidence from ICIs therapy in cancer patients with CKD, including those who are renal transplantation recipients or have end-stage renal disease (ESRD). Additionally, the promising targeted immunotherapy for malignant tumors is expected to improve both renal outcomes and survival prognosis in cancer patients.